Performance of carbide insert in turning of titanium alloy under carbon dioxide cryogenic cooling - Mat, Siti Asiyah (2021)
In manufacturing industries, such as aerospace, automotive, chemical and medical, the application of titanium alloys has received more attention, especially in dental implant and orthopedic implant. Although this titanium alloy has a unique characteristics, such as difficulties to machining due to high hardness, lower thermal conductivity and higher chemical reactivity, this material is always in high demand. During machining of titanium alloy, the major issues frequently discussed are rapid cutting tool wear and generation of high cutting temperature. The proper cooling method needs to be used in order to reduce high cutting temperature that causes rapid tool wear thus increases the tool life of the cutting tool during machining titanium alloy. Many studies have been reported by researchers of cryogenic cooling in machining titanium. In this research, an attempt has been made to investigate the effect of cryogenic cooling using carbon dioxide (CO2) liquid, when it is applied to the workpiece and cutting tool during turning of titanium alloy Ti–6Al–4V ELI. The operation process was carried out using a 3-axis CNC Haas ST-20 lathe machine. Response Surface Methodology (RSM) has been used to design the experiment in determining the effect of the cutting parameters: cutting speed, feed rate and depth of cut towards tool life of the uncoated carbide insert. From RSM, Box-Behnken design has been selected to arrange the cutting parameters of cutting speed with range of 120 to 220 m/min, feed rate with 0.1 to 0.2 mm/rev and depth of cut is 0.4 to 0.6 mm. The flank wear was measured using tool maker microscope. The cutting time values were recorded for each 20 mm on the workpiece until flank wear (Vb) reaches the tool life criterion followed by JIS B4011-1971 standard. From the experiment, the longest tool life recorded is 17.58 minutes obtained at cutting speed 120 m/min, feed rate 0.15 mm/rev and depth of cut 0.40 mm. The shortest tool life is 0.45 minutes obtained at the cutting speed 220 m/min, feed rate 0.15 mm/rev and depth of cut 0.6 mm. The ANOVA analysis showed that for tool life, cutting speed is the most significant factor followed by feed rate and depth of cut to determine and optimise the tool life values. From the detailed observation using SEM, it can be concluded the tool failure mode presents at the cutting tool are flank wear and crater wear. In addition, the observed dominant wear mechanism at the cutting tool is abrasion and adhesion.